The art of enlivening - water installations in renaissance gardens - Gryglewski, Piotr (Ars inspiratio: Studies dedicated to Professor Eleonora Jedlińska, 2024)
Water is crucial to the functioning of garden settings. The ways in which it is obtained and supplied have always played an important role. They combined purely technical elements with the decoration of the gardens themselves. These systems included water reservoirs, fountains or cascades, playing a decorative role while at the same time improving the whole system of distributing the necessary water. During the Renaissance, building on the experience of earlier eras, these skills were creatively developed. Among these, the most interesting are the hydraulic systems known from Rome, Naples or the Medici residences. The solutions applied there in the 16th century also influenced Polish founders.